An infrared interactive patient position guidance and acquisition control system for use during radiotherapy treatment. Issue 3 (6th April 2017) - Fuse, Hiraku; Komatsu, Kenji; Arakawa, Hiroyuki; Sakae, Takeji; Tatsuya, Fujisaki
Abstract: Background: The control of patient position, posture and respiratory movements during radiotherapy is important for effective and specific treatment of malignancy. We have developed an infrared (IR) interactive patient position guidance and acquisition control system for clinical use, comprising IR cameras, IR markers and dedicated software. Materials and methods: We evaluated the system with ten healthy volunteers and ten experienced operators. IR markers were placed on the body surface. Their positions were calculated using vectors of three translational and three rotational parameters, and the intrafractional error for each marker was acquired with and without respiratory motion. The inclusion of multiple positioning markers allowed for real-time visualisation of the patient posture, with feedback on misalignment and required postural adjustments. Results: The positioning time was 73 seconds (with a minimum period of 39 seconds), which was significantly shorter than for conventional line alignment. A comparison of positioning reproducibility between conventional line alignment and this system was <3·5 mm and was not patient dependent or operator dependent. An intrafractional error of displacement of up to 10·0 mm was found in the right iliac crest. Conclusions: This IR interactive system was shown to be high utility and suitable for monitoring patient position, posture and respiratory movements during radiotherapy.